Do HIV risk and prevention behaviors change over time among adults in permanent supportive housing?. Issue 9 (2nd September 2019) - Wenzel, Suzanne L.; Rhoades, Harmony; La Motte-Kerr, Wichada; Duan, Lei; Harris, Taylor; Rice, Eric; Henwood, Benjamin F.
ABSTRACT: Persons experiencing homelessness have a disproportionate burden of HIV infection and high rates of HIV risk behavior. Permanent supportive housing (PSH) has been identified as a primary solution to homelessness, but little is known about HIV sexual risk behavior among persons in PSH, nor about how HIV risk and prevention behavior may change as persons move from homelessness into PSH. Utilizing longitudinal data from 421 persons prior to moving in and over their first year living in PSH, this study assesses change over time in HIV risk and prevention behavior utilizing generalized linear mixed models. Results reveal changes in sexual risk behavior over time, including an overall increase in the rate of sexual activity, but a decrease in rates of some sexual risk behaviors, including condomless sex and multiple partners. While decreasing overall, the prevalence of condomless sex remains high (63%) at 12-months. Combined with a precipitous drop in HIV prevention programming exposure (from 56% at baseline to 23% at 12-months), only two-thirds of those sexually active reporting a past year HIV test at 12-months post-housing, and rare use of PrEP, these findings suggest a need for additional attention to promotion of sexual health behaviors and HIV prevention within PSH.